Thermal robustness evaluation of nonvolatile memory using Pt nanogaps. (26th July 2018) - Naitoh, Yasuhisa; Suga, Hiroshi; Abe, Takuya; Otsu, Kazuki; Umeta, Yukiya; Sumiya, Touru; Shima, Hisashi; Tsukagoshi, Kazuhito; Akinaga, Hiroyuki
Abstract: We investigated the thermal robustness of a nonvolatile memory using polycrystalline platinum (Pt) nanogap electrodes. The temperature dependences of resistance states were evaluated from room temperature to 773 K. At high temperatures, the resistance of the high-resistance state (HRS) was slightly altered as the temperature changed. This slight alteration could be neglected, and the thermal robustness was improved by etching a SiO2 layer just under the nanogap. This indicated that the thermal alteration was caused by current leakage through the SiO2 layer. The nonvolatile memory employing Pt nanogaps is expected to be potentially useful as a thermally robust memory up to 773 K.